A novel family with Lamin B1 duplication associated with adult-onset leucoencephalopathy. Issue 2 (16th January 2009) - Brussino, A; Vaula, G; Cagnoli, C; Mauro, A; Pradotto, L; Daniele, D; Di Gregorio, E; Barberis, M; Arduino, C; Squadrone, S; Abete, M C; Migone, N; et al.
Abstract : Background and aim: Duplication of the lamin B1 gene ( LMNB1 ) has recently been described in a rare form of autosomal dominant adult-onset leucoencephalopathy. The aim of the study was to evaluate the presence of LMNB1 gene defects in a series of eight patients with diffuse adult-onset hereditary leucoencephalopathy. Methods: Clinical features of tested patients included a variable combination of pyramidal, cerebellar, cognitive and autonomic dysfunction. Neuroradiological data (MRI) showed symmetrical and diffuse white-matter lesions in six cases, and multifocal confluent lesions in two. LMNB1 full gene deletion/duplication and point mutations were searched using a TaqMan real-time PCR assay and direct sequencing of all coding exons. Results: One patient carried a 140–190 kb duplication involving the entire LMNB1 gene, the AX748201 transcript and the 3′ end of the MARCH3 gene. Clinical and neuroimaging data of this proband and an affected relative overlapped with the features already described in patients with LMNB1 duplication. Lamin B1 expression was found increased in lymphoblasts. No LMNB1 gene defect was identified in the remaining seven probands. Conclusions: LMNB1 gene duplication appears characteristic of a subset of adult-onset autosomal dominant leucoencephalopathies, sharing autonomic dysfunction at onset, diffuse T2-hyperintensity of supra- and infratentorial white matter, sparing of U-fibres and optic radiations. The variable phenotypes in the remaining cases lacking LMNB1 defects (five with autosomal dominant transmission) suggest that adult-onset leucoencephalopathies are genetically heterogeneous.